Artificial opal photonic crystals and inverse opal structures – fundamentals and applications from optics to energy storage. Issue 24 (28th June 2015) - Armstrong, Eileen; O'Dwyer, Colm
<x xml:space="preserve">Abstract</x> This review outlines the fundamentals and applications of artificial opal photonic crystals, their fabrication, development and adaption from optics to energy storage research.